2004
DOI: 10.1111/j.1582-4934.2004.tb00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional changes in rat hippocampal slice cultures after short‐term oxygen‐glucose deprivation

Abstract: To study effects of short‐term cerebral ischemia, hippocampal slice cultures were subjected to oxygen and glucose deprivation (OGD) followed by a period of normoxic reoxygenation. Propidium iodide staining, and MTT/formazanassay were used to evaluate cell viability and metabolic activity. CA1 pyramidal cells were analyzed at the light‐and electron microscopic levels. Cell damage was found to be insignificant during the first hour after 10 min OGD but profound following 4 h, showing delayed neuronal cell damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 38 publications
1
22
0
3
Order By: Relevance
“…Oxygen-glucose deprivation (OGD) paradigm was used to model ischemia in vitro. The cultures were placed in the interface chamber filled with N 2 and perfused with a medium containing 10 mM sucrose instead of glucose for 10 min (Jourdain et al, 2002;Lushnikova et al, 2004). After that, they were washed with warm regular culture medium, placed back in the normal conditions in the incubator for 15 min or 2 h, and fixed and processed for electron microscopy (EM).…”
Section: In Vitro Brain Ischemia Modelingmentioning
confidence: 99%
“…Oxygen-glucose deprivation (OGD) paradigm was used to model ischemia in vitro. The cultures were placed in the interface chamber filled with N 2 and perfused with a medium containing 10 mM sucrose instead of glucose for 10 min (Jourdain et al, 2002;Lushnikova et al, 2004). After that, they were washed with warm regular culture medium, placed back in the normal conditions in the incubator for 15 min or 2 h, and fixed and processed for electron microscopy (EM).…”
Section: In Vitro Brain Ischemia Modelingmentioning
confidence: 99%
“…Unlike long-term deprivation that causes irreversible cell death, transient OGD induces mild and reversible damage such as decreased metabolic activity (Lushnikova et al, 2004), inhibition of transmitter release (Fowler, 1989), and increased postsynaptic Ca 2ϩ influx, spontaneous miniature EPSC amplitude, evoked AMPA and NMDA receptor-mediated excitatory responses, and AMPA/NMDA responses ratio (Quintana et al, 2006). The impact of OGD was evaluated by measuring f-EPSPs evoked in area CA1 by electrical stimulation of Schaffer collaterals (Raley-Susman and Lipton, 1990;Lobner and Lipton, 1993).…”
Section: Pharmacological and Genetic Inhibition Of Pp1 Reduces Recovementioning
confidence: 99%
“…The somata of СА1 neurons possessed a typical pyramidal shape. As was mentioned above, the slices under study were subjected to 10-min-long OGD with subsequent normoxic reoxygenation for 1 h. In our previous studies, we found that in such case neurons in the СА1 area undergo gradual delayed significant structural damage [2]. These delayed destructive consequences are based on certain primary reactions and mechanisms, in particular disorders of biochemical cascades providing production of adenosine triphosphate (ATP), disorders of the processes of ion exchange, significant excessive release of glutamate, accumulation of Са 2+ in the cells, intensification of oxidative processes, etc.…”
Section: Resultsmentioning
confidence: 99%
“…To induce the state of LTP, we arranged episodes of OGD using a technique described earlier [2,3]. The duration of these episodes was 10 min; then, the slices were returned to normal conditions of culturing for 1 h (period of normoxic reoxygenation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation